Interrupting and overlapping in the US presidential debates - a comparative study - Viljanen, Janita (My University, 2019)
This thesis studied the occurrence of overlapping and power-oriented interruptions in the presidential debates of USA. The study was conducted by comparing the debates of the 2012 and 2016 presidential elections and its aim was to provide an image of the developmental direction of interrupting in the presidential debates. The theoretical frame was constituted on “An analysis in terms of relationally neutral, power- and rapport-oriented acts” by Julia A Goldberg (1990) and “A simplest systematics for the organization of turn-taking for conversation” by Harvey Sacks et al. (1974). The main alignment of the study was Julia Goldberg’s poweroriented interruptions and its two subheadings “content control interruptions” and “process control interruptions”. In the study it was found that the power-oriented interruptions were more prevalent in the 2016 elections than in the 2012 elections. The difference was most visible in the prevalence of content-control interruptions as there was a major increase in their number in 2016 debates.